2020
DOI: 10.1021/acs.energyfuels.0c02443
|View full text |Cite
|
Sign up to set email alerts
|

New Molecular Insights into Aggregation of Pure and Mixed Asphaltenes in the Presence of n-Octylphenol Inhibitor

Abstract: Asphaltene stability can be perturbed during the oil production and transportation, leading to asphaltene precipitation and deposition. Chemical inhibitors are usually added to the oil phase to postpone asphaltene deposition. The chemical bonding between asphaltene and inhibitor molecules, and the steric hindrance are the key mechanisms of aggregation inhibition. Nevertheless, the interaction mechanisms between asphaltenes and chemical inhibitors still need more research investigations. In this paper, we use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 103 publications
1
48
0
Order By: Relevance
“…In this research, two asphaltene structures with the continental structure, which is a dominant type of asphaltene structure, 40 are adopted from our previous studies to investigate the formation of hydrogen bonds. 41 Asphaltene 2 (A2) is a continental asphaltene with the potency to form hydrogen bonds due to having hydroxyl and pyridine groups, while asphaltene 3 (A3) is a similar continental asphaltene with no potential for forming hydrogen bonds (Figure 2). Also, the impact of two inhibitors, including a surfactant, namely n-octylphenol (OP), and an IL, namely 1butyl-3-methylimidazolium chloride, on asphaltene deposition in the asphaltene/n-heptane solution is studied.…”
Section: Methodology and Computational Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, two asphaltene structures with the continental structure, which is a dominant type of asphaltene structure, 40 are adopted from our previous studies to investigate the formation of hydrogen bonds. 41 Asphaltene 2 (A2) is a continental asphaltene with the potency to form hydrogen bonds due to having hydroxyl and pyridine groups, while asphaltene 3 (A3) is a similar continental asphaltene with no potential for forming hydrogen bonds (Figure 2). Also, the impact of two inhibitors, including a surfactant, namely n-octylphenol (OP), and an IL, namely 1butyl-3-methylimidazolium chloride, on asphaltene deposition in the asphaltene/n-heptane solution is studied.…”
Section: Methodology and Computational Approachmentioning
confidence: 99%
“…The distance between the closest atoms with a cutoff threshold of 0.35 nm is considered the aggregation criterion for asphaltene. 41 The z-averaged aggregation number (g z ) quantifies the aggregate size along the simulation time (see eq 2). 27,41 This analysis is implemented with an in-house python script using the MDAnalysis package and the output coordinates of asphaltene molecules after the GROMACS simulation.…”
Section: Energy Evaluationmentioning
confidence: 99%
“…Common dispersants include small molecules, polymers, and ionic liquids. As for small molecules, the intermolecular force between sodium dodecyl benzene sulfonate, sodium dodecyl sulfate (SDS), and asphaltenes was studied. It is found that the van der Waals force between benzene ring surfactants and asphaltenes is greater than SDS without benzene rings. In addition, octylphenol can form a strong hydrogen bond with asphaltene and inhibit asphaltene aggregation …”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al 12 found that hydrophobic ionic liquids can dissolve and disperse asphaltenes well. Ghamartale et al 13 presented that surfactants, such as n-octylphenol (OP), are more effective in reducing the aggregation of continental asphaltenes with hydroxyl and pyridine groups, while metal ions introduced through nanoparticles are undesirable in the process of crude oil refining. Ionic liquids are expensive; surfactants will dissolve in water; and their efficacy is reduced.…”
Section: Introductionmentioning
confidence: 99%